Palladium-Catalysed Intramolecular C–N versus C–C Coupling: The Effect of 1,8-peri-Interaction in the Naphthalene System - Debnath, Sudarshan; Mondal, Shovan (SynOpen, 2019)
Palladium-catalysed competitive intramolecular C–N and C–C coupling of 2-amino-2′-bromodiarylsulfones has been carried out based on 1,8-peri-interactions for the synthesis of phenothiazinedioxide and benzonaphthathiophenedioxide derivatives. A DFT study has been performed that provides support for the influence of the 1,8-peri-interaction.
Keywords: naphthalene; 1,8-peri-interaction; cyclization; fused-ring; heterocycles